Two-dimensional half-strong real moment problem and the corresponding block matrices. Part I - Dudkin , M. E.; Dyuzhenkova , O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
УДК 517.9 The relationship between the classical moment problem and the spectral theory of Jacobi matrices is generalized. We present the solution of the two-dimensional half-strong moment problem and suggest an analog of Jacobi-type matrices associated with the two-dimensional half-strong moment problem and the corresponding system of polynomials orthogonal with respect to a measure with compact support in the real plane.